Dok Rumah / Siti Fairuz Ibrahim - Ibrahim, Siti Fairuz (Faculty of Art and Design, 2021)
The motivational typography Dok Rumah #Toksah Merayap manifests itself visually as an awareness campaign on how to simply stay at home to protect us due to the Covid-19 pandemic, but in Kedah dialect. The government had issued a movement control order to prevent people from moving and becoming infected. Currently the most followed platform for Coronavirus awareness campaigns is on social media, followed by television and print media. The Coronavirus awareness campaign through typography is essential for the people of Kedah to have knowledge and awareness of the spread and prevent disease outbreaks. Actually, it helps dispel COVID-19 just with Dok Rumah #Toksah Merayap. The purpose of this campaign is to educate people of Kedah state in their own dialect so that the message is conveyed clearly to the people as the COVID-19 pandemic has been affecting the world badly and impacting people’s lives to change 360 degrees. Staying at home is challenging. There were 8,663 confirmed cases of COVID-19 in Malaysia as of July 6, 2020. As the situation worsened, Prime Minister Muhyiddin Yassin enacted the Movement Control Ordinance which was extended to May 12, 2020, and Malaysia is officially in the Recovery MCO from June 10, 2020 to August 31, 2020.